Compliance of Quezon City Public Library, Marikina City Public Library and National Library's Library for the Blind to IFLA guidelines for libraries for persons with disabilities - Diaz, Guadalupe Maxima B.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Public Libraries are heralds of knowledge for all people. These are libraries which cater to the needs of all - students, elderly, professionals, normal citizens and the disabled. These institutions answer the information needs and queries of every citizen, including those who are physically disabled. This study is aimed at evaluating selected public libraries in NCR and assess if these chosen public libraries adhere to the guidelines set by IFLA in terms of the construction and development of public libraries in order to cater physically disabled users.
The researcher assessed and evaluated three public libraries - Marikina Public Library, Library for the Blind of the National Library and the newly constructed Quezon City Public Library. In this study, the physical access, services and materials and how they communicate with disabled users where evaluated based on the IFLA's Guidelines to Access to Libraries for Persons with Disabilities.
The results of the study revealed the numerous obstacles faced by the institution in order to develop a PWD-friendly library - lack of budget, lack of information and interest and lack of services available for these users. Furthermore, the results, as compared to a study in Singapore, also mentioned the lack of initiative of the local government as one of the hindrances for developing such public library.
Thesis (Bachelor of Library and Information Science)
Keywords: Libraries and people with disabilities -- Standards; Libraries and the blind -- Standards; Blind -- Services for; People with disabilities -- Services for -- Standards